2018
DOI: 10.1108/jcm-08-2016-1919
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with “enemy-brothers”: Sunni Arab consumers’ animosity toward Iran and Turkey

Abstract: Purpose This paper aims to examine the causes and consequences of animosity that Sunni Arabs may harbor against Iran and Turkey – two regional powers and key players in the Middle East. Design/methodology/approach Using Jordanians as proxy for Sunni Arab consumers, data were collected from 218 respondents by means of an intercept survey. A systematic random sampling was used in selecting the respondents. Structural equation modeling was used to examine the role of religious/sectarian commitment (Sunni Islamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
4
14
0
Order By: Relevance
“…This theory can explain the behavior of group members toward another group(s); as such, in our study, the ethnic Malay is the in-group, whereas the Chinese are the out-group. Similar studies previously on consumer ethnocentrism and consumer animosity also used SIT as their theoretical basis (Ganideh and Elahee, 2016;Sierra and McQuitty, 2007;Verlegh, 2007;Zeugner-Roth et al, 2015) to explain the conceptual roots of consumer ethnocentrism and consumer animosity as the alternate antecedents to consumer behavior.…”
Section: Social Identity Theorymentioning
confidence: 97%
“…This theory can explain the behavior of group members toward another group(s); as such, in our study, the ethnic Malay is the in-group, whereas the Chinese are the out-group. Similar studies previously on consumer ethnocentrism and consumer animosity also used SIT as their theoretical basis (Ganideh and Elahee, 2016;Sierra and McQuitty, 2007;Verlegh, 2007;Zeugner-Roth et al, 2015) to explain the conceptual roots of consumer ethnocentrism and consumer animosity as the alternate antecedents to consumer behavior.…”
Section: Social Identity Theorymentioning
confidence: 97%
“…The benefit above remains highly important to the product manufacturers who are either incapable or unwilling to export their products. Finally, despite decades of research discussing the effects of both religion and religiosity on consumers' purchase choices (e.g., Abosag & Farah, 2014;Al Ganideh & Elahee, 2018;Deb & Sinha, 2016;Farah & El Samad, 2014;Farah & Newman, 2010), this field remains underexplored. Accordingly, identifying the links between religion, religiosity, and ethnocentrism could be the venue for further analyses bearing in mind the major difference between the two terms.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…A number of scholars investigated the link between animosity and various social attributes, such as patriotism (Ganideh and Elahee 2018; Ishii 2009), exclusionism (Ishii 2009), dogmatism (Shoham et al 2006), nationalism (Ganideh and Elahee 2018; Shoham et al 2006), internationalism (Ganideh and Elahee 2018; Ishii 2009; Shoham et al 2006), and cosmopolitanism (Park and Yoon 2017). In general, their studies indicated that patriotism, dogmatism, nationalism, and exclusionism enhance consumer animosity, whereas cosmopolitanism and internationalism are negatively associated with antipathy toward foreign countries.…”
Section: Previous Researchmentioning
confidence: 99%
“…Many recent investigations (e.g., Funk et al 2010; Ganideh and Elahee 2018; Maher and Mady 2010) similarly found a negative link between consumer animosity and willingness to buy products from the disliked nation, and a few others suggested that consumer antipathy also influences product judgments (Huang, Phau, and Lin 2010; Ishii 2009), preference for domestic products/products from one’s in-group (Heinberg 2017; Shimp, Dunn, and Klein 2004), willingness to pay a price premium for products from one’s in-group (Shimp, Dunn, and Klein 2004), and country-of-origin image (Hoffmann, Mai, and Smirnova 2011). Notably, some studies (e.g., Klein, Ettenson, and Morris 1998; Klein 2002; Mostafa 2010) examined the effect of willingness to buy on product ownership and reported a strong association.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation